Handoff process simulation by network simulator 2 in mobile telematic networks with IPv6 - Gelvez García, Nancy Yaneth; López Sarmiento, Danilo Alfonso; Herrera Cubides, Jhon Francined (TECCIENCIA, 2014)
This article presents the handoff process in MIPv6 communication networks, where the system QoS parameters can be defined from the process latency. To display the process the NS-2 2.31 with Mobiwan patch was used; This Simulator allows implementing protocols that are similar to those used in MIPv6 and similarly can generate traffic and represent network node mobility.